Ability of metformin to deplete NAD+ contributes to cancer cell susceptibility to metformin cytotoxicity and is dependent on NAMPT expression - Zhuang, Yongxian; Haugrud, Allison B.; Schaefer, Meg A.; Messerli, Shanta M.; Miskimins, W. Keith (Frontiers in Oncology, 2023)
Background: Nicotinamide adenine dinucleotide (NAD+) is vital for not only energy metabolism but also signaling pathways. A major source of NAD+ depletion is the activation of Poly (ADP-Ribose) Polymerase (PARP) in response to DNA damage. We have previously demonstrated that metformin can cause both caspase-dependent cell death and PARP-dependent cell death in the MCF7 breast cancer cells but not in the MDA-MB-231(231) breast cancer cells while in high glucose media. We hypothesize that depletion of NAD+ in MCF7 cells via activation of PARP contributes to the cell death caused by metformin. Nicotinamide phosphoribosyltransferase (NAMPT), a key rate-limiting step in converting nicotinamide (vitamin B3) into NAD+, is essential for regenerating NAD+ for normal cellular processes.Evidence shows that overexpression of NAMPT is associated with tumorigenesis. We hypothesize that NAMPT expression may determine the extent to which cancer cells are sensitive to metformin.